Family values and the regulation of labor - Alberto Alesina; Yann Algan; Pierre Cahuc; Paola Giuliano (Institute for the Study of Labor (IZA), 2010)
Flexible labor markets require geographically mobile workers to be efficient. Otherwise, firms can take advantage of the immobility of workers and extract monopsony rents. In cultures with strong family ties, moving away from home is costly. Thus, individuals with strong family ties rationally choose regulated labor markets to avoid moving and limiting the monopsony power of firms, even though regulation generates lower employment and income. Empirically, we do find that individuals who inherit stronger family ties are less mobile, have lower wages, are less often employed and support more stringent labor market regulations. There are also positive cross-country correlations between the strength of family ties and labor market rigidities. Finally, we find positive correlations between labor market rigidities at the beginning of the twenty first century and family values prevailing before World War II, which suggests that labor market regulations have deep cultural roots.
Keywords: E0; P16; Z10; Z13; 330; Family values; labor regulation; Arbeitnehmerschutz; Arbeitsmarktflexibilisierung; Familiensoziologie; Soziale Werte; Arbeitsmobilität; Welt